Once a Boertjie, always a Boertjie? a poststructuralist study of written English-Afrikaans code-switching. - Kotze, Leonie (My University, 2013)
This study analyses the social meanings of Afrikaans in post-apartheid South Africa by examining the use of Afrikaans in social phenomena such as ethnicity, race, class and politics in written English-Afrikaans code-switching in the Sunday Times during the period January to June 2009. This study arose as a consequence of the observation that the continued use of Afrikaans in an English-medium newspaper, sixteen years after the first South African democratic elections, might be somewhat unusual, particularly given that Afrikaans was the main vehicle through which Afrikaner nationalism and apartheid were established and maintained. Although Afrikaner nationalism and apartheid as a state ideology fell away after the 1994 South African democratic elections, Afrikaans is generally perceived as a marker of apartheid and oppression. The continued use of Afrikaans is also somewhat surprising given that English has always carried more prestige than Afrikaans. Against this backdrop, the study draws upon Irvine and Gal’s notions of indexicality, iconization, fractal recursivity and erasure to illustrate that Afrikaans has been employed mainly to highlight and criticise negative social and political aspects in South African society such as unacceptable behaviour by politicians or losing a cricket/rugby/football match. The study also illustrates that Afrikaans is associated mainly with the ethnic group ‘Afrikaners’, which in turn is associated with ‘backwardness’, ‘whiteness’, ‘rurality,’ ‘racism’, ‘apartheid’ and ‘aggression’. Furthermore, the study shows the relevance of the sociopolitical and sociolinguistic history of South Africa for the various associations of the current use of Afrikaans in English-language media.